Growth hormone-mediated janus associated kinase-signal transducers and activators of transcription signaling in the growth hormone-resistant potassium-deficient rat - Schaefer, Franz; Yoon, Sun-Ae; Nouri, Pouneh; Tsao, Tanny; Tummala, Padmaja; Deng, Ellen; Rabkin, Ralph (Journal of the American Society of Nephrology, 2004)
Potassium deficiency (KD) is associated with severe growth failure, in part caused by growth hormone (GH) resistance. This study set out to determine whether the resistance could be caused by a defect in GH-mediated janus associated kinase-signal transducers and activators of transcription (STAT) signaling as occurs in uremia.